Pemeriksaan Payudara Sendiri (SADARI) Pada Wanita Usia Subur Dalam Upaya Pencegahan Terjadinya Risiko Kanker Payudara Di Wilayah Kerja Puskesmas Pagar Agung Lahat Tahun 2017 - Purnama, Rizka (IKEMAS: Jurnal Ilmu Kesehatan Masyarakat, 2018)
Cancer is a malignant neoplasm disease that has a very wide and complex spectrum. Almost no cancer can be cured spontaneously. Every minute there is 1 person in the world who died of cancer, every 3 minutes there is one new cancer patients. The high prevalence of cancer in Indonesia needs to be observed with early prevention and detection measures that have been done by health care providers. Cases of cancer found in early stages and get a fast and appropriate treatment will provide healing and life expectancy longer.Therefore, it is important to do regular checkups regularly as an effort to prevent and early detection of cancer The purpose of research is Knowledge of knowledge, age, education , attitudes, and the role of officers with the risk of breast cancer against breast self-examination at Puskesmas Pus Agung Lahat in 2017. The method used in this study is quantitative with cross sectional design. The samples in this study were women of childbearing age in Pagar Agung Puskes area as much as 77 respondents. The sampling technique used was non random sampling. Data analysis was done univariat, bivariate with chi square and multivariate test with logistic regression test. Based on the result of the research, it is found that knowledge (pValue = 0,018), age (pValue = 0,800), attitude (pValue = 0,000) and officer role (pValue = 0,005) to behavior of BSE in Puskesmas Puskesmas Lahat. Multivariate analysis result shows that role officer variable (pValue = 0,005) is the most dominant variable. From the research results can be concluded that there is a significant relationship between the knowledge and the role of officers against the behavior of BSE in the community at the Pus Agung Lahat Public Health Center. From the results of the study it is suggested that health workers can improve their knowledge and roles through training and extension activities.